Modeling of the linear thermoviscoelastic behavior of rib-reinforced polyfoams. The structural model - Yankovskii, Andrey Petrovich (Computational Continuum Mechanics, 2012)
The paper presents a numerical-analytical technique for modeling the thermoviscoelastic behavior of rib-reinforced polyfoams. The proposed approach allows us to consider, at discrete moments of time, such composition as an initially stressed thermoelastic material with reduced effective elastic and temperature stiffness.